Integrating network analysis and experimental validation to reveal the ferroptosis-associated mechanism of acteoside in the treatment of diabetic nephropathy - Luo, Zheng; Zhang, Shu-Jiao; Tang, Jing-Yi; Deng, Yuanyuan; Kang, Yi; Zhang, Xing-Hua; Lu, Hong-Mei; Wang, Yao-Xian; Liu, Wei-Jing; Ma, Yu (Frontiers in Pharmacology, 2025)
BackgroundActeoside (ACT), a natural phenylethanoid glycoside extracted from the Rehmannia glutinosa, has demonstrated renal protective effects against diabetic nephropathy (DN) through its confirmed antioxidant and anti-inflammatory properties. However, the underlying mechanisms by which ACT regulates DN progression via targeting ferroptosis remain to be elucidated.PurposeThis study aims to elucidate whether ACT ameliorates DN in mice by targeting ferroptosis and to uncover the underlying mechanisms involved.MethodsThis study first utilized network pharmacology approaches, integrating multiple databases and bioinformatics tools, to predict and screen the potential targets and pathways of ACT in DN. To validate the therapeutic efficacy of ACT, a DN model was established in C57BL/6J mice using streptozotocin (STZ). Subsequently, the therapeutic effect of ACT on DN was verified through molecular experiments. Finally, molecular docking was adopted to further verify the binding ability between ACT and key targets.ResultsNetwork pharmacology analysis identified potential targets of ACT related to DN and revealed that its therapeutic effects may be mediated through the regulation of ferroptosis. In vivo experiments demonstrated that ACT exerts significant renoprotective effects by improving renal function and alleviating pathological damage in DN mice. Furthermore, ACT was shown to attenuate oxidative stress by restoring mitochondrial homeostasis, a process closely associated with the regulation of ferroptosis.ConclusionIn summary, this study provides preclinical evidence that ACT ameliorates DN through ferroptosis inhibition, positioning it as a novel therapeutic candidate for DN treatment.